2018
DOI: 10.3390/fermentation4010017
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of pH and Temperature on Arachidonic Acid Production by Glycerol-Grown Mortierella alpina NRRL-A-10995

Abstract: Arachidonic acid (AA) has a wide range of applications in medicine, pharmacology, diet, infant nutrition, and agriculture, due to its unique biological properties. The microbiological processes involved in AA production usually require carbohydrate substrates. In this paper, we propose a method for AA production from glycerol, an inexpensive and renewable carbon substrate that is produced by the fungal strain, Mortierella alpina NRRL-A-10995. Our experimental results showed that the optimum pH values required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…These results support the importance of pH as a limiting factor for fungal lipid production. These results also agree with the recent findings that pH 6.0 was the most suitable pH for arachidonic acid and biomass production by Mortierella alpine (Mironov et al, 2018).…”
Section: Influence Of Initial Ph On the Fungal Biomass And Lipid Prodsupporting
confidence: 93%
“…These results support the importance of pH as a limiting factor for fungal lipid production. These results also agree with the recent findings that pH 6.0 was the most suitable pH for arachidonic acid and biomass production by Mortierella alpine (Mironov et al, 2018).…”
Section: Influence Of Initial Ph On the Fungal Biomass And Lipid Prodsupporting
confidence: 93%
“…Lipid accumulation, as well as biomass formation, can be affected by many different cultivation parameters, such as the nutrient composition of the growth medium, temperature, pH, aeration, or parameter shift during the fermentation (temperature/pH) [ 2 , 21 , 22 ]. Optimization of the nutrient composition of the growth medium is one of the most important aspects in improving fungal lipid production.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, GLA proportion (25.4 ± 1.3% in TFA) in the engineered A. oryzae culture grown at the optimal CSH medium was higher than that found in the same fungal strain (9.5-16.0% GLA in TFA) (Chutrakul et al, 2016) and the known GLA-producing strains of Zygomycete fungi, such as Mucor rouxii (18.1% GLA in TFA), Cunninghamella sp. (11.9% GLA in TFA), and Mortierella alpina (1.6-6.1% GLA in TFA) (Kavadia et al, 2001;Jeennor et al, 2006;Mironov et al, 2018). Our results revealed that the change in fatty acid phenotypes might be attained by cell acclimatization in the optimal medium apart from the influence of genetic manipulation.…”
Section: Strains Parameters Referencesmentioning
confidence: 67%